Some Similarities and Differences Between the Observed Alfvénic Fluctuations in the Fast Solar Wind and Navier–Stokes Turbulence - Borovsky, Joseph E.; Mina, Tiziano (Frontiers in Astronomy and Space Sciences, 2020)
Abstract: Using two long data sets analyzed on equal footing, the properties of Alfvénic fluctuations in the fast (coronal-hole-origin) solar wind and Navier-stokes turbulence are compared. A 26.4-s-long interval of hot-wire measurements in the ONERA wind tunnel is used and a 71-hr-long interval of unperturbed coronal-hole plasma measured by the WIND spacecraft at 1 AU is used. Similarities and differences between a Navier-Stokes fluid and the collisionless magnetized solar-wind plasma are discussed, as are differences between the physical natures of the advecting evolving turbulent fluctuations and the propagating non-evolving Alfvénic fluctuations. The details of the power spectral densities of the turbulence and the Alfvénic fluctuations are compared. Statistics of first and second time derivatives are examined for the wind-tunnel and solar-wind time series and the statistics are compared with the statistics of time derivatives of phase-randomized time series. Using running medians, the statistics of flat spots in the time series of Alfvénic fluctuations is examined, which is evidence of a cellular structure to the magnetic field and velocity field. A call for a campaign of expanded coordinated future work is made.